AN ANALYSIS OF DECLARATIVE SPEECH ACT IN HANSEL AND GRETEL: WITCH HUNTER MOVIE - Sandi Frandes Malau; Erika Sinambela; Jubil Ezer Sihite (Sean Institute, 2022)
This study aim to determine the types of declarative speech act found in Hansel and Gretel: Witch Hunter movie, and also to find the dominant types of declarative speech act in the movie. Qualitative research is defined as a research method that focuses on obtaining data through open-ended and conversational communication. Qualitative research is a means for exploring and understanding the meaning individuals or group ascribe to a social human problem (Creswell : 2012)There are 4 types of declarative speech acts found in the movie. That is consisting in declarative speech act namely Command, Order, Request, and Suggestion. The most dominant type of declarative speech act used is Command. There were 48 declarative data taken from transcript Hansel and Gretel : Witch Hunter Movie. It consisted of 23 (48%) for Command, 10 (21%) for Order, 5 (10,41%) for Request, and 10 (21%) for Suggestion. The most dominant declarative specch acts in this transcript was Command with the total amount 23 (48%). The writer concludes that the most dominant declarative acts in the movie is command, which means that the characters in the story prefer everything to run quickly, command is a declarative speech act message that wants the recipient of the message to be able to immediately do what the speaker says. Learning pragmatics, particularly speech acts, can help readers avoid misunderstandings of meaning that can occur throughout the teaching and learning process or while communicating with others.